TWO STAY-TWO STRAY (TS-TS) MENINGKATKAN KETERAMPILAN BERBICARA UNTUK MENGULAS FILM - Mujiyanti Mujiyanti (Universitas Veteran Bangun Nusantara, 2020)
This study aims to describe the application of the two stay two stray (TS-TS) learning model to improve students' speaking skills in film review material. One of the advantages of the two stay two stray (TS-TS) learning model is that it is able to train students' speaking skills comprehensively, namely through the opportunity for home group discussions, the role of the home team and guest team, and in class discussions presenting the results of group work. The research subjects were class VIIIB students of SMP Negeri 1 Samigaluh even semester of the 2018/2019 academic year. This type of research is classroom action research. The researcher used systematic observation and achievement tests; and the instruments were in the form of anecdotal records, check lists, and learning outcome test questions for the data collection techniques. The results of the study were (1) there was an increase in students 'speaking skills through the application of the two stay two stray (TS-TS) learning model of 34.38% on students' speaking skills mastery in the initial or pre-cycle conditions, 39.84% in the first cycle, and 90.63% in the second cycle and (2) there was an increase in student learning outcomes through TS-TS of 43.48% in learning completeness at the pre-cycle stage, 69.57% in the first cycle, and 86 , 96% in the second cycle.